Comportamiento agronómico del cultivo de cebolla roja (Alliun cepa l.) Con diferentes abonos orgánicos en la unidad educativa calazacón de Santo Domingo de los Tsáchilas, año 2014 - Romero Guamán, Guido Oswaldo (2015)
This research was conducted in Education Unit Calazacón of Santo Domingo de los Tsáchilas, 2014. Located at Km 6.5 Vía Quevedo left margin. Design Randomized Complete Block (DBCA), with seven treatments and four replications. The variables evaluated were: length and number of leaves at 15, 30 and 45 days; Bulb weight (g) at harvest and Bulb diameter (cm) The results are: the agronomic performance of red onion (Alliun cepa L.) was determined in leaves along at 15, 30 and 45 days in treatment 3 (5 kg of humus) with 30,26 and 44,90 and 60 , 78 cm. Number of leaves at 15, 30 and 45 days with 4.25; 4.90 and 5.49 leaves. The highest level of organic fertilizer in the production of red onion (Alliun cepa L.) was treatment 3 (5 kg of humus) with 5.51 cm diameter bulb and bulb weight with 110.41 g. The economic analysis of the treatments under study demonstrated that major revenues are in treatment 3 (5 kg of Humus) to $ 107.21; net income to $ 35.78 and benefit cost $ 0.33.